STUDY OF THE CAUSES OF SPORTS INJURIES AMONG FOOTBALL GOALKEEPERS IN BABYLON GOVERNORATE - Obeidi, Ali Hassan al (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The purpose of this study was to determine the most common types of sports injuries among Jordanian soccer goalkeepers, the most common locations of injury in the body, the time of injury (game and training), the type of injury (artificial turf, natural grass, or sand), and the cause of injury. The results showed that the most common type of injury was muscle tear (28.88%), followed by wrist (21.28%), while the most common injury sites for goalkeepers were head (29.39%), wrist (8.45%) and fingers (8.45%). Injuries sustained during training were more common than injuries sustained during matches (52.36%), compared to 47.64% of injuries sustained during matches. The most common comments related to submitted injuries were submitted turf (44.43%) artificial (43.92%) and more in submitted sand (11.66%). The most common cause of injury was lack of medical checks (13.18%), followed by lack of sports rehabilitation techniques (11.82%). According to the results of this study, the researchers recommend more attention to comprehensive medical checks (having all athletes undergo medical checks, maintaining safe processes in training and competition, and regular field maintenance).